Prenatal Diagnosis of a Fetal Epidural Hematoma - Tikvica Luetic, A.; Habek, D.; Stanojevic, M.; Miric Tesanic, D.; Padovan-Stern, R. (Zeitschrift für Geburtshilfe und Neonatologie, 2016)
A fetal epidural hematoma is a rare finding during the prenatal period, with different etiologies such as maternal trauma, infections, or maternal use of specific medications such as warfarin. Both ultrasonography and magnetic resonance imaging (MRI) have been used successfully to evaluate the fetal central nervous system. Although these methods are also useful in detecting and evaluating a fetal epidural hematoma, brain function of the neonate cannot be exactly predicted on the basis of the prenatal findings. According to the literature data to date, this is the first reported case of prenatally detected fetal epidural hematoma of unknown etiology with a good outcome.
Keywords: fetal epidural hematoma; prenatal diagnostics; prenatal sonography; prenatal MRI; positive postnatal outcome